Minor and Trace Element Emissions from Post-Combustion CO2 Capture from Coal: Experimental and Equilibrium Calculations - Cotton, Alissa; Patchigolla, Kumar; Oakey, John E. (Elsevier Science B.V., Amsterdam., 2014)
Elemental partitioning, including gaseous elemental emissions from pilot scale (25 kWth), post combustion CO2 capture using a Ca-based sorbent, have been investigated for naturally occurring elemental impurities found in limestone, that have the potential to be released to the environment under carbonation and calcination conditions. Inductively Coupled Plasma - Mass Spectrometry (ICP-MS) analysis of Longcliffe SP52 limestone was undertaken to identify other impurities present, and the effect of sorbent mass and SO2 concentration on elemental partitioning in the carbonator between solid sorbent and gaseous phase was investigated, using a bubbler sampling system. Samples were analysed using ICP-MS, which showed that sorbent mass and SO2 concentration in the carbonator effected the concentrations of gaseous trace elements sampled. Thermodynamic modelling of the carbonation and calcination process was also undertaken, based on molar quantities of trace elements identified from ICP-MS analysis of limestone, which provided useful information with regards to element stability and partitioning under realistic CO2 capture conditions.